The Relationship Between Workplace Spirituality and Transfer of Training - Mohd Rosli, Nur Amalina; Ismail, Fadillah; Johar, Siti Sarawati; Mior Ahmad Ridzuan, Muhammad Fateh; Abdul Kadir, Adibah (Online Journal for TVET Practitioners, 2019)
Abstract: Nowadays, the demand of skilled workers in Malaysia has increased based on the increased automation and introduction to the latest technology for the Industrial Revolution 4.0. As a result, the organizations have to look into the ways to effectively engage their employees and utilize their full potential by enhancing positive transfer of training. However, review of literature revealed that so far, no study had been conducted between workplace spirituality towards transfer of training. The current study aims to investigate relationship between workplace spirituality and the transfer of training. To achieve the objectives of this study, a quantitative research design where the questionnaire will be used to address the problem. The study will use the whole population of the study from the employees involved in the â€œstandard of procedureâ€ training in one month at all X company branches in Malaysia to collect data using adapted questionnaire. Further, this data is statistically tested using Statistical Packages for Social Sciences for Windows Version (SPSS) version 25.0 for empirical investigations of the relationships between workplace spirituality and transfer of training. The expected findings of this study are the significant relationship between workplace spirituality dimensions and transfer of training. Results of the study imply that organizations should encourage employees to apply the importance of workplace spirituality in the employees so that they understand the concept of working properly in order to improve the organizational management function to encourage the betterment of the workforce.